Highly selective dual-band interdigital bandpass filter for C-band applications - Zakaria El Ouadi; Asma Khabba; Jamal Amadid; Saida Ibnyaich; Abdelouhab Zeroual; Tole Sutikno (Universitas Ahmad Dahlan, 2024)
Miniaturization in the telecommunications field is deemed a current challenge and a critical demand in order to improve communication quality between the transmitter and the receiver while avoiding clutter issues. The main objective of this work is to design a miniature interdigital bandpass filter (IBF) using planar technology. The proposed bandpass filter is made up of three equidistant parallel-coupled lines carefully deposited on a small Rogers-5880 substrate possessing a full dimension of 10×10×1.6 mm3, a relative permittivity =2.2, and a loss tangen of 0.0009. The proposed IBF has been designed and simulated using the HFSS software, which is a simulator that studies the electromagnetic behavior of radio frequency structures using cutting-edge finite element solvers. The reached outcomes present good electrical performance in terms of insertion loss , reflection coefficient , voltage standing wave ratio (VSWR), and selectivity, making the proposed IBF suitable for integration in small electronic devices for C-band applications (4 GHz to 8 GHz).